The Influence of Price and Coffee Shop Atmosphere on Coffee Shop Consumer Satisfaction in Sampit City - Eko Cahyo Purnomo; Hari Susanto; Deky Prasetyo; Sylva Rulliansyah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study aims to analyze the influence of price and atmosphere on consumer satisfaction at Coffee 1999 in Sampit City. The research method used is a quantitative approach with data collection through questionnaires to respondents who are Coffee 1999 customers. The data analysis technique uses multiple linear regression analysis with t-test (partial), F-test (simultaneous), and coefficient of determination (R²). The results of the study show that: (1) the price variable has a positive and significant effect on consumer satisfaction with a calculated t-value (3.655) > t-table (2.02809) and significance (0.001 < 0.05); (2) the atmosphere variable also has a significant effect on consumer satisfaction with a calculated t-value (2.337) > t-table (2.02809) and significance (0.025 < 0.05); and (3) the results of the simultaneous test show that price and atmosphere together have a significant effect on consumer satisfaction with an F-count value (31.152) > F-table (3.26) and significance (0.000 < 0.05). The R² value of 0.627 indicates that the two independent variables influence consumer satisfaction by 62.7%, while the remaining 37.3% is influenced by other variables. This study confirms that the implementation of the right pricing strategy and the creation of a comfortable café atmosphere are important factors in building and maintaining customer satisfaction.